2004
DOI: 10.1124/mol.104.004515
|View full text |Cite
|
Sign up to set email alerts
|

Tibolone Is Metabolized by the 3α/3β-Hydroxysteroid Dehydrogenase Activities of the Four Human Isozymes of the Aldo-Keto Reductase 1C Subfamily: Inversion of Stereospecificity with a Δ5(10)-3-Ketosteroid

Abstract: Tibolone is used to treat climacteric complaints and prevent osteoporosis. These beneficial effects are exerted via its 3␣-and 3␤-hydroxymetabolites. Undesirable stimulation of the breast and endometrium is not apparent. Endometrial stimulation is prevented by the progestogenic activity of its ⌬ 4 -ene metabolite. The enzymes responsible for the formation of these active metabolites are unknown. Human aldo-keto reductase (AKR)1C isoforms have been shown to act as 3␣/3␤-hydroxysteroid dehydrogenases (HSDs) on 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 36 publications
4
61
1
1
Order By: Relevance
“…Recently it has been shown that the ketosteroid dehydrogenase enzymes of the AKR1C family are capable of metabolizing the 3hydroxy-tibolone metabolites 19 . Although AKR1C1, AKR1C3, and AKR1C4 act as reductases, the AKR1C2 enzyme is capable of oxidizing the 3β-OH-tibolone metabolite back to tibolone.…”
Section: Expression Of Akr1c Enzymes In Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been shown that the ketosteroid dehydrogenase enzymes of the AKR1C family are capable of metabolizing the 3hydroxy-tibolone metabolites 19 . Although AKR1C1, AKR1C3, and AKR1C4 act as reductases, the AKR1C2 enzyme is capable of oxidizing the 3β-OH-tibolone metabolite back to tibolone.…”
Section: Expression Of Akr1c Enzymes In Culturesmentioning
confidence: 99%
“…We show that the stromal and epithelial cells express the ketosteroid dehydrogenase AKR1C2, which may allow for the conversion of 3βOH-tibolone back to tibolone 19 . From our observations, using the co-culture system, we conclude that tibolone counteracts E 2 -driven proliferation in the uterus in a manner similar to progestins, and that the balance of metabolism of tibolone in the endometrium favors the production of the progestagenic metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that over time 3b-hydroxy tibolone is converted back into D 4 -tibolone (Schatz et al 2005). However, our array data show that, like MPA, they are tibolone's own progestagenic properties which are responsible for an increased expression of the aldo-keto reductase family 1 member C1 (AKR1C1, an enzyme that catalyzes the formation of 3b-hydroxy tibolone exclusively) (Steckelbroeck et al 2004). …”
Section: Discussionmentioning
confidence: 86%
“…Conversion of TIB into 3α-or 3β-hydroxytibolone depends on the tissue where its metabolism occurs. In peripheral tissues, AKR1C1 and AKR1C2 form 3β-hydroxytibolone which exhibits estrogenic activity, whereas in liver, TIB is reduced to 3α-hydroxytibolone by AKR1C4 which functions predominantly as 3α-hydroxysteroid dehydrogenase (Steckelbroeck et al 2004). This explains why 3α-hydroxytibolone is the major circulating metabolite, whereas 3β-hydroxytibolone is the major metabolite in target tissues (Penning et al 2014).…”
Section: Metabolism Of Progestinsmentioning
confidence: 90%
“…Interestingly, AKR1C2 exhibits different stereochemical preference depending on the ketosteroid substrate. Indeed, it produces 3α-products with the potent androgen 5α-dihydrotestosterone (5α-DHT) behaving as an efficient 3α-hydroxysteroid dehydrogenase, whereas it inverts its stereospecificity with TIB acting as a 3β-hydroxysteroid dehydrogenase (Steckelbroeck et al 2004, Rižner & Penning 2014. Finally, TIB can also be metabolized, in less amount, to the potent estrogen 7α-methylethinylestradiol (Wiegratz et al 2002).…”
Section: Metabolism Of Progestinsmentioning
confidence: 99%